Ethnic differences in quality of life and its association with survival in patients with heart failure. Issue 9 (20th June 2020) - Stein, Gillian; Teng, Tiew‐Hwa K.; Tay, Wan T.; Richards, A. Mark; Doughty, Robert; Dong, YanHong; Sim, David; Yeo, Poh S. D.; Jaufeerally, Fazlur; Leong, Gerard; Soon, Dinna; Ling, Lieng H.; et al.
Abstract: Background: Optimizing quality of life (QoL) is a key priority in the management of heart failure (HF). Hypothesis: To investigate ethnic differences in QoL and its association with 1‐year survival among patients with HF. Methods: A prospective nationwide cohort (n = 1070, mean age: 62 years, 24.5% women) of Chinese (62.3%), Malay (26.7%) and Indian (10.9%) ethnicities from Singapore, QoL was assessed using the Minnesota Living with HF Questionnaire (MLHFQ) at baseline and 6 months. Patients were followed for all‐cause mortality. Results: At baseline, Chinese had a lower (better) mean MLHFQ total score (29.1 ± 21.6) vs Malays (38.5 ± 23.9) and Indians (41.7 ± 24.5); P  < .001. NYHA class was the strongest independent predictor of MLHFQ scores (12.7 increment for class III/IV vs I/II; P  < .001). After multivariable adjustment (including NT‐proBNP levels, medications), ethnicity remained an independent predictor of QoL ( P  < .001). Crude 1‐year mortality in the overall cohort was 16.5%. A 10‐point increase of the physical component (of MLHFQ) was associated with a hazard (HR 1.22, 95% 1.03‐1.43) of 1‐year mortality ( P = .018) in the overall cohort. An interaction between MLHFQ and ethnicity was found ( P = .019), where poor MLHFQ score (per 10‐point increase) predicted higher adjusted mortality only in Chinese (total score: HR 1.18 [95% CI 1.07‐1.30]; physical: HR 1.44 [95% CI 1.17‐1.75]; emotional score: HR 1.45 [95% CI 1.05‐2.00]). Conclusions: Ethnicity is an independent determinant of QoL in HF. Despite better baseline QoL in Chinese, QoL was more strongly related to survival in Chinese vs Malays and Indians. These findings have implications for HF trials that use patient‐reported outcomes as endpoints.